Union Leaders' language during conflict: Does gender matter? - Charles Keim; Yonatan Reshef (The Institute of Academic Research and Publication (IARP), 2021)
We analyze the language used by two consecutive British Columbia Teachers’ Federation (BCTF) presidents, Susan Lambert and Jim Iker, during two collective bargaining sessions that pitted the BCTF against the British Columbia (BC) government and the British Columbia Public School Employers’ Association (BCPSEA). Our study analyzes how gender language differences if they indeed exist, are manifested during critical moments that require strong leadership. Language is a critical resource for leaders, who use it to define issues, assign motives and inspire action, and portray themselves as people of power and consequence. Both women and men can employ a variety of linguistic strategies and the linguistic decisions that male and female leaders make provide a window onto if and how gender may be manifested by those in power and how they use language to present themselves as effective leaders. In this paper, we explore whether and how gender influences the linguistic choices of a male and female union leader during times of conflict.